2018
DOI: 10.1108/bij-07-2017-0204
|View full text |Cite
|
Sign up to set email alerts
|

Agentic work behaviour and thriving at work: role of decision making authority

Abstract: Purpose The purpose of this paper is to examine the contribution of agentic work behaviour and decision-making authority (DMA) to thriving at work and, more importantly, the moderating role of DMA in the relationship between agentic behaviour and thriving. Design/methodology/approach The study has been carried out upon a random sample of 330 employees below supervisory level from manufacturing companies located at Odisha (a state located at the eastern part of India). After verifying the significance of corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 60 publications
(53 reference statements)
4
45
2
Order By: Relevance
“…These findings, thus, corroborated hypothesis 1, which predicted a positive impact of participative decisionmaking on thriving at work. These results are in the direction of a previous study that demonstrated the positive effects of participative decision making on thriving at work (Sia & Duari, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings, thus, corroborated hypothesis 1, which predicted a positive impact of participative decisionmaking on thriving at work. These results are in the direction of a previous study that demonstrated the positive effects of participative decision making on thriving at work (Sia & Duari, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…According to the model of Spreitzer et al (2005), contextual factors, such as participation in decision making, are characterized as triggers of thriving at work. In this sense, organizations that give their employees greater freedom to make their own decisions and implement their ideas at work contribute to increasing their motivating energy at work, which leads them to explore and learn new skills (Sia & Duari, 2018). Therefore, this finding provides empirical support for that theory, as it was found that participation in decision making acted as a factor in the labor context that positively impacts thriving at work.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Lastly, a research done by Sia and Duari (2018) found that decision making had a positive effect on the employees since they were given a freedom to give ideas and this provides them with a sense of control in the final decision. Heponiemi et al (2014) also found that decision authority was something positive in an organization, and employees can make their own decision to resign when they feel like their certain jobs are too stressful.…”
Section: Decision Authoritymentioning
confidence: 99%
“…The results showed that the positive effect on the employees made them be more confident, thus, would increase their job performance. To investigate the impact of decision-making authority on performance, Sia and Duari (2018) had proven that decision making had a positive effect on employees. When employees were given a chance to share their ideas and have a sense of control in making the final decision, they became more confident to perform their jobs.…”
Section: Introductionmentioning
confidence: 99%